2008
DOI: 10.1007/s10164-008-0127-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of allosuckling in wild guanacos (Lama guanicoe)

Abstract: Although allosuckling, the lactation of non-filial offspring, can be a costly behavior, it has been reported in several species across a wide range of mammalian orders. Monotocous species such as ungulates exhibit this behavior less frequently than polytocous species, and most cases have been reported among captive specimens. A case of allosuckling of a free-ranging guanaco (Lama guanicoe) calf is reported. Allosuckling observed in this species may represent opportunistic behavior by the calf, supporting the '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Instead, the herd stayed together and never used the whole paddock area at the same time. Moreover, allonursing was recorded recently in a free‐ranging population of guanacos (Zapata et al. 2009), an unusual piece of evidence that has been reported in only half ungulate species in which allonursing has been reported (for a review see Víchová 2003).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Instead, the herd stayed together and never used the whole paddock area at the same time. Moreover, allonursing was recorded recently in a free‐ranging population of guanacos (Zapata et al. 2009), an unusual piece of evidence that has been reported in only half ungulate species in which allonursing has been reported (for a review see Víchová 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Among South American camelids, allonursing has been observed in free ranging (Zapata et al. 2009) and captive guanacos (Zapata et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kin selection hypothesis did not seem to be a major factor in this study, as the females were not related to each another. Based on the findings of Zapata et al [19], [20] on another camelid, the guanaco, we predicted the milk-theft hypothesis be the main cause why the camel calves sucked from non-maternal females. If this was valid we predicted that (i) a calf would suck from the non-maternal dam standing in other than antiparallel sucking position so that it was more difficult for the dam to distinguish the calf's identity or to threat the non-filial calf.…”
Section: Introductionmentioning
confidence: 88%
“…However, allosuckling has been described in other camelids. Zapata et al [19] reported incidental allosuckling occurrence in wild guanacos ( Lama guanicoe ) and regular occurrence of allosuckling in captive farmed guanacos as behaviours that were consistent with the milk-theft hypothesis and a compensation theory [20], [21].…”
Section: Introductionmentioning
confidence: 99%